A year with Thomas Merton - Montaldo, Jonathan (San Francisco Harper & Row, 2004)
"Join Thomas Merton in a spiritual journey as you read selections from his journal. This elegant and intimate daily companion offers his wisdom and spiritual guidance with selections attuned to the seasons and to the movements of Merton's own life - fro
Keywords: Catholic Church -- Prayers and devotions -- English. Devotional calendars -- Catholic Church. Catholic Church